Specialty Nursing Organizations: Opportunities for Perioperative Excellence - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2021)
Specialty nursing organizations are described as those for specific practice areas (e. g. geriatrics) within nursing. Members share similar interests, or a passion for a specialty area, and come together to create a group or pursue membership in an established specialty group. This paper describes the evolution of specialty nursing organizations and how they represent specific areas of nursing practice. The benefits of membership shall be described using Operating Room Nurses Association (ORNAC) and the Saskatchewan periOperative Registered Nurses Group (SORNG) to demonstrate examples.